Failure analysis on the connecting rod by finite element method - Andoko, A. (American Institute of Physics Inc., 2020)
Increasing the volume of combustible motor vehicles, needs to be anticipated as early as possible if there is a failure on the combustion engine components. Failure that may occur on the component is the connecting rod. This study aims to determine the cause of the failure of a connecting rod in the car. The method used in this study is a finite element method (FEM) simulation. The simulation results show that, cracks that are near the big end have greater stress and strain values than the area far from. Â© 2020 American Institute of Physics Inc.. All rights reserved.